Distinct genetic influences on grammar and phonological short-term memory deficits: evidence from 6-year-old twins. - Bishop, D; Adams, C; Norbury, C (2006)
Children with language impairments have limitations of phonological short-term memory (STM) and have distinctive problems with certain aspects of grammar. Both deficits have been proposed as phenotypic markers of heritable language impairment. We studied 173 twin pairs, selected to be over-representative of children with risk of developmental language impairment, using a battery of standardized language and intelligence tests, a test of nonword repetition to index phonological STM and two elicitation tasks to assess use of verb tense marking. As predicted, the phonological STM and the verb tense measures both discriminated children with risk of language impairment from low risk children, and DeFries-Fulker analysis showed that impairments on both tasks were significantly heritable. However, there was minimal phenotypic and etiological overlap between the two deficits, suggesting that different genes are implicated in causing these two kinds of language difficulty. From an evolutionary perspective, these data are consistent with the view that language is a complex function that depends on multiple underlying skills with distinct genetic origins.